The Hybrid Poetological Model in Peter Handke's Work: Intertextuality, Language Innovation and Cultural Border Crossings - Glišič, Miša (Cultural Arts Research and Development, 2025)
This article presents an innovative, Hybrid Poetological Model for analyzing the works of Peter Handke. Drawing on Julia Kristeva’s “Revolution of Poetic Language”, it integrates linguistic, visual and semiotic elements to interpret Handke’s intricate aesthetic and cultural expressions. Focusing on intertextuality, the model examines the interaction between two language registers: the semiotic, which encompasses rhythm, sound, figurative language, and unconventional structures, and the symbolic, which reflects social norms, cultural identities, and historical contexts. The model emphasizes that this interplay is essential for comprehending Handke’s linguistic innovations, particularly his exploration of hybridity through visual and semiotic influences. Handke’s adoption of Hölderlin’s meditations on nature and Cézanne’s painterly fragmentation translates visual techniques into poetic textures, challenging traditional boundaries and creating layered narratives across cultural spaces. His adoption of American semiotics further expands aesthetic possibilities by employing sign-based frameworks. Since the late 1980s, Handke’s stylistic innovations, such as fragmentation, minimalism and meta-poetry, have demonstrated a radical shift towards experimental and avantgarde practices. This interdisciplinary study aims to analyze Handke’s texts, offering new interpretive perspectives that emphasize critique and reflection. The model emphasizes the interconnectedness of aesthetic, social and cultural dimensions, aligning with Kristeva’s vision of poetic revolution. This transdisciplinary approach can be applied to other authors, thereby enriching our understanding of modern literary aesthetics and cultural negotiations.